MARKETING IN TOURISM: NEED, FEATURES AND PERSPECTIVES - Mushtai, Valentyna (Sworld-Us Conference proceedings, 2023)
The work indicates the importance of marketing in the activities of modern tourist enterprises. The main reasons for the development of marketing in tourism are indicated, and its essence is revealed. It is substantiated that the peculiarities of marketin